Reflex testing for Lynch syndrome: if we build it, will they come? Lessons learned from the uptake of clinical genetics services by individuals with newly diagnosed colorectal cancer (CRC) - Tomiak, E; Samson, A; Spector, N; Mackey, M; Gilpin, C; Smith, E; Jonker, D; Allanson, J; Asmis, T (Université d'Ottawa | University of Ottawa, 2013)
The aim of this qualitative study was to examine the experience of individuals facing a choice about genetic counselling/testing in the context of newly diagnosed colorectal cancer (CRC). Nineteen individuals with newly diagnosed CRC, including 12 individuals who accepted genetic counselling ("acceptors") and 7 individuals who declined genetic counselling ("refusers"), were interviewed using a standardized questionnaire guide which focused on motivations and barriers experienced in the decision process. Data were analyzed using Karlsson's Empirical Phenomenological method of data analysis (Karlsson in Psychological qualitative research from a phenomenological perspective. Almgvist and Wiksell International, Stockholm, 1993). Three major themes were identified: facing challenges in health literacy; mapping an unknown territory; and adjusting to cancer. The study participants' testimonies provided novel insights into potential reasons for patient non-engagement in pilot studies of reflex testing for Lynch syndrome, and allowed us to formulate several recommendations for enhancing patient engagement. Our study findings suggest that patient engagement in clinical cancer genetics services, including reflex testing for Lynch syndrome, can only be achieved by addressing current health literacy issues, by deconstructing current misconceptions related to potential abuses of genetic information, by emphasizing the clinical utility of genetic assessment, and by adapting genetics practices to the specific context of cancer care.
Keywords: Colorectal cancer; Lynch syndrome; Genetic counselling; Patient engagement; Universal screening; Health literacy